Structural performance of high-strength-concrete columns reinforced with GFRP bars and ties subjected to eccentric loads. (15th April 2019) - Salah-Eldin, Ashraf; Mohamed, Hamdy M.; Benmokrane, Brahim
Highlights: Structural behavior of HSC columns reinforced with GFRP bars and ties. Failure mechanisms of HSC columns reinforced with GFRP bars and ties. Assessing the compressive contribution of GFRP bars in HSC columns. Developing the P-M interaction diagram of GFRP reinforced HSC columns. Abstract: In recent decades, high-strength concrete (HSC) has been widely used in bridge elements, tunnels, and precast-concrete members. Only a limited number of studies, however, have investigated the structural behavior of HSC columns reinforced with glass-fiber-reinforced-polymer (GFRP) bars. Moreover, most concrete codes do not explicitly cover concrete with strengths above 55 MPa. This paper investigates the structural behavior of HSC columns reinforced with GFRP bars and ties when subjected to eccentrically axial loads. Eight full-scale concrete columns with a 400 × 400 mm cross section and 2000 mm in height were tested under axial monotonic loading. The test variables were the eccentricity-to-width ratio, concrete strength, and reinforcement type using steel and GFRP bars and ties. The test results indicate that the failure of the test specimens under different levels of eccentricity was not triggered by rupture of the GFRP bars on the tension side, up to attaining the maximum section capacity governed by concrete-strain limitation. The load–axial displacement, load–lateral displacement, failure mode, and reinforcement strain responses of all the GFRP-reinforced HSC columns are presented and compared to that of the steel-reinforced HSC columns. The structural behavior of HSC columns reinforced with GFRP bars and ties subjected to eccentric axial loads were evaluated by drawing axial force–flexural moment interaction diagrams and comparing them to that for the steel-reinforced columns. An analytical method (layer-by-layer approach) was applied to predict the axial- and flexural-load capacity of the GFRP-reinforced HSC columns. A parametric study was used to examine the effect of increasing the reinforcement ratio and concrete strength and to investigate the strength contribution of GFRP compression bars.